The psychological distance of climate change - Spence, Alexa; Poortinga, Wouter; Pidgeon, Nick (Blackwell-synergy, 2012)
Avoiding dangerous climate change is one of the most urgent social risk issues we face today and understanding related public perceptions is critical to engaging the public with the major societal transformations required in order to combat climate change. Analyses of public perceptions have indicated that climate change is perceived as distant on a number of different dimensions. However to date there has been no in depth exploration of the psychological distance of climate change. This study uses a nationally representative UK sample in order to systematically explore and characterise each of the four theorised dimensions of psychological distance – temporal, social and geographical distance, and uncertainty in relation to climate change. We examine how each of these different aspects of distance relates to each other as well as to concerns about climate change and sustainable behaviour intentions. Results indicate that climate change is actually both psychologically distant and proximal in relation to different dimensions. Lower psychological distance was generally associated with higher levels of concern; although certain aspects of greater psychological distance (perceptions of disproportionate impacts of climate change on developing countries) were also significantly related to preparedness to act on climate change. Findings support the idea that it is useful for risk communications regarding climate change to highlight both local and distant impacts of climate change where appropriate. Interestingly, our data indicates that whilst psychological distance communications are likely to be valuable in promoting concern about climate change, these may also be useful in promoting action amongst those already concerned about climate change.